2019
DOI: 10.1039/c9nj02790d
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic hydrogen production using [FeFe]-hydrogenase mimics based on tetracene derivatives

Abstract: The synthesis, structure, physical properties, and electrocatalytic hydrogen production of tetrathiatetracene ligand based [FeFe]-hydrogenase mimic molecules were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…14 For several years, extensive efforts have been devoted to designing structural and functional models so as to mimic the protonation and redox properties of the H-cluster. [15][16][17][18][19][20][21][22][23][24] These models include a variety of dithiolato ligands, μ-(SCH2)2X, in which the central atom/group X could be NR, CR2, O, S, SnR2 or (Ph)P=O ( Figure 1B). [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Moreover, several research groups have reported approaches for introducing strong σ-donor ligands, such as phosphines and phosphites, at the diiron core to enhance the protophilicity of the model complexes ( Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…14 For several years, extensive efforts have been devoted to designing structural and functional models so as to mimic the protonation and redox properties of the H-cluster. [15][16][17][18][19][20][21][22][23][24] These models include a variety of dithiolato ligands, μ-(SCH2)2X, in which the central atom/group X could be NR, CR2, O, S, SnR2 or (Ph)P=O ( Figure 1B). [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Moreover, several research groups have reported approaches for introducing strong σ-donor ligands, such as phosphines and phosphites, at the diiron core to enhance the protophilicity of the model complexes ( Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…During the last few decades, numerous synthetic approaches have been designed to mimic the protonation and redox properties of the natural archetype [19–33] . It is worth pointing out that the nature of the central atom/group in the bridging dithiolato linkers has a significant role in determining the electronic/steric properties of such artificial H‐cluster mimics [34–38] .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] During the last few decades, numerous synthetic approaches have been designed to mimic the protonation and redox properties of the natural archetype. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] It is worth pointing out that the nature of the central atom/group in the bridging dithiolato linkers has a significant role in determining the electronic/steric properties of such artificial H-cluster mimics. [34][35][36][37][38] For example, the presence of group 14 elements at the bridgehead atom of [Fe 2 (CO) 6 {μ-(SCH 2 ) 2 EMe 2 }] (E = C, Si, Ge and Sn) complexes results in increasing the electron density at the FeÀ Fe vector.…”
Section: Introductionmentioning
confidence: 99%
“…For several years, extensive efforts have been devoted to designing structural and functional models so as to mimic the protonation and redox properties of the H-cluster. [15][16][17][18][19][20][21][22][23][24] These models include a variety of dithiolato ligands, μ-(SCH2)2X, in which the central atom/group X could be NR, CR2, O, S, SnR2 or (Ph)P=O (Figure 1B). [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Moreover, several research groups have reported approaches for introducing strong σ-donor ligands, such as phosphines and phosphites, at the diiron core to enhance the protophilicity of the model complexes (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%